A method of constructing the frame of a directed graph - Hofuku, Ichiro; Oshima, Kunio (Zielona Góra: Uniwersytet Zielonogórski)
In web search engines, such as Google, the ranking of a particular keyword is determined by mathematical tools, e.g., Pagerank or Hits. However, as the size of the network increases, it becomes increasingly difficult to use keyword ranking to quickly find the information required by an individual user. One reason for this phenomenon is the interference of superfluous information with the link structure.
Keywords: directed graph; node clustering; Perron-Frobenius theorem; information retrieval